2017
DOI: 10.1007/s11274-017-2307-5
|View full text |Cite
|
Sign up to set email alerts
|

Functional metagenomics of oil-impacted mangrove sediments reveals high abundance of hydrolases of biotechnological interest

Abstract: Mangroves are located in coastal wetlands and are susceptible to the consequences of oil spills, what may threaten the diversity of microorganisms responsible for the nutrient cycling and the consequent ecosystem functioning. Previous reports show that high concentration of oil favors the incidence of epoxide hydrolases and haloalkane dehalogenases in mangroves. This finding has guided the goals of this study in an attempt to broaden the analysis to other hydrolases and thereby verify whether oil contamination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 49 publications
2
10
0
Order By: Relevance
“…In addition, several thermostable cellulases were also isolated (Kalaiselvi et al 2013;Naresh et al 2019). Meanwhile, based on metagenomic approaches, bacteria belonging to three phyla, Proteobacteria, Firmicutes and Actinobacteria were detected as cellulose-degrading bacteria, and a novel β-glucosidase and a endoglucanase were cloned and characterized (Li et al 2012;Mai et al 2014;Thompson et al 2013;Ottoni et al 2017). Besides that, Numerous genes encoding cellulose-degrading enzymes, such as, endo-1,4-D -glucanase (cellulase) and β-glucosidase were found in metagenome datasets from Matang Mangrove Forest Reserve (Priya et al 2018).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, several thermostable cellulases were also isolated (Kalaiselvi et al 2013;Naresh et al 2019). Meanwhile, based on metagenomic approaches, bacteria belonging to three phyla, Proteobacteria, Firmicutes and Actinobacteria were detected as cellulose-degrading bacteria, and a novel β-glucosidase and a endoglucanase were cloned and characterized (Li et al 2012;Mai et al 2014;Thompson et al 2013;Ottoni et al 2017). Besides that, Numerous genes encoding cellulose-degrading enzymes, such as, endo-1,4-D -glucanase (cellulase) and β-glucosidase were found in metagenome datasets from Matang Mangrove Forest Reserve (Priya et al 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Ottoni and colleagues conducted taxonomic analysis of the hydrolase sequences including cellulase in fosmid library constructed from mangrove sediment in São Paulo state, Bertioga, Brazil (Ottoni et al 2017). As a result of the analysis, cellulase related to the families Pseudomonadaceae and Thermoanaerobacteraceae were the most abundant.…”
Section: Degradation Mechanisms Of Cellulose Hemicellulose and Pectinmentioning
confidence: 99%
“…The culture-dependent method is a classical strategy for bioprospecting enzymes from environmental samples [12]. However, the necessity to reproduce requirements for microbial growth in laboratory conditions is a limitation of this approach [13]; thus, new strategies for bioprospecting have been driven by culture-independent methods, such as functional screening from metagenomic libraries constructed using environmental DNA [14]. This method favors the discovery of enzymes from uncultivated microorganisms without performing a cultivation step [15].…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…The present study aimed to identify genes and microorganisms from mangrove samples that were able to produce xylanases and amylases, either using approaches dependent and independent of cultivation. Based on previous studies that explored the mangrove sediments as biotechnological source [14,[19][20][21], the study hypothesized that the conditions found in mangrove areas, mainly the high salinity, could select for organisms harboring genes and enzymes of high industrial interest and these enzymes could be recovered by applying culture-dependent and cultureindependent methods.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…Functional metagenomics is a multi-step experimental approach that uses expression libraries encoding isolated DNA of mixed microbial populations for the transformation of a relevant host microorganism. Transformed clones can subsequently be selected for a broad range of phenotypes of interest, e.g., enzymatic activities such as lipo-, haemo- or hydrolytic activities (Henne et al, 2000; Rondon et al, 2000; Ottoni et al, 2017). This potentially results in the discovery of novel candidate enzymes that are encoded in the original microbial population.…”
Section: Introductionmentioning
confidence: 99%